Holistic assessment of women with hyperemesis gravidarum: A randomised controlled trial. Issue 11 (November 2015) - Fletcher, S.J.; Waterman, H.; Nelson, L.; Carter, L.A.; Dwyer, L.; Roberts, C.; Torgerson, D.; Kitchener, H.
Abstract Background Hyperemesis gravidarum or severe nausea and vomiting of pregnancy affects women's physical, social and psychological wellbeing and often requires frequent hospital admissions. Current standard care may be too medically focussed to meet all of women's complex needs. Aim The aim of this study is to test where using a validated questionnaire, the Hyperemesis Impact of Symptoms tool, delivered by a nurse to assess the overall effect of hyperemesis on an individual woman's life and to provide advice tailored to her specific needs, will help her cope better with her symptoms and reduce admissions to hospital. Design This study was a two arm randomised controlled trial in which women with hyperemesis from four hospitals were randomly allocated to one of two groups: (1) usual care and (2) usual care plus assessment with the Hyperemesis Impact of Symptoms questionnaire and a care plan tailored to their responses. Participants and methods Recruitment was from women who were admitted with hyperemesis gravidarum; diabetic women or those over 14 weeks gestation were excluded. Those who consented completed questionnaires to assess their quality of life and the severity of symptoms at baseline and at three time points over the following 6 weeks. Results Women's average social functioning, Hyperemesis Impact of Symptom scores and average number of admissions were not significantly different between either group. The average number of days in hospital for the questionnaire and tailored plan group was significantly lower, 4.97, compared with 6.14 in the usual care group. Using the questionnaire to plan individualised care was not associated with significant reduction in health care costs. Conclusion Using the Hyperemesis Impact of Symptoms questionnaire to tailor a care plan to address women's individual needs was not associated with any significant improvements in the quality of life. The cost effectiveness analysis did not indicate that the questionnaire is cost saving. The Hyperemesis Impact of Symptoms questionnaire is a practical tool for nurses and midwives to assess the overall impact of hyperemesis gravidarum on the individual and could be useful for assessing symptoms and evaluating physical, social and psychological changes following treatment in either clinical or research settings.